The recurrence interval of forest fires in Cabeço da Vaca (Cabreira Mountain - northwest of Portugal) - Leite, Flora Ferreira (2011)
The recurrence of forest fires is degrading an important part of the Portuguese natural heritage namely its forest and soils. In this paper we present the case study of Cabeço da Vaca (Cabreira Mountain—northwest Portugal), where in recent decades, particularly in the 70s, there was a significant increase in the number of forest fires and in the areas scorched annually. There is thus a turning point between a period when fire was an integral part of the ecosystems and when fire has become a serious threat to woodland management and development (Bento Gonçalves, 2006). Starting with a thorough characterization of forest fires and based on the mapping of scorched areas between 1990 and 2006, we have proceeded to identify the annual pattern of maximum recurrence and the definition of the return interval in Cabeço da Vaca, producing thus a valuable document to support management and forestry development in general.